The Emergence and the Development of the Female voice in Postcolonial Kenyan Fiction - (:unkn) unknown (My University, 2009)
This study of Kenyan literature, which focuses specifically on female writers, is based on the premise that female writers, though prolific, have for a long time been neglected by literary critics, and even when focused upon, are lumped together with other so-called ‘Third world’ female writers. Thus, the idiosyncrasies in their particular works are very often overlooked. This study seeks to correct this by undertaking an in-depth study of each of the novels explored, while at the same time using each of them to undertake a study of the Kenyan society with particular attention to the situation of the woman as depicted in the texts. The novel, which is here the primary source, is examined as a cultural tool. Given the large number of novels that have been written by Kenyan women writers, this study uses a case-oriented methodology to select a few novels that are used as representative samples for Kenyan writing by women. The texts selecte! d cover a long time period; published from the mid-sixties just after Kenya’s independence, to the outset of the present millennium. The study is guided by theories that are drawn from postcolonial studies, cultural studies, and gender studies. It is our hope that this study gives a comprehensive state of the art survey on the Kenyan novel, with a specific focus on the state of the Kenyan woman, thus clearing the way for similar studies to be carried out on women writers not only in Kenya, but in the other countries in the East African region and the African continent at large.
Keywords: African Research